2010
DOI: 10.1016/j.whi.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' Perceptions of Barriers to Providing Dental Care to Pregnant Women

Abstract: Purpose-The purpose of the study was to understand US dentists' attitudes, knowledge, and practices regarding dental care for pregnant women and to determine the impact of recent papers on oral health and pregnancy and guidelines disseminated widely. [2006][2007], the investigators conducted a mailed survey of all 1,604 general dentists in Oregon; 55.2% responded). Structural equation modeling was used to estimate associations between dentists' attitudes toward providing care to pregnant women, dentists' knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 22 publications
(18 reference statements)
4
59
0
5
Order By: Relevance
“…However, oral health during pregnancy can affect the pregnancy outcome too (3,4). Preterm birth is one potential complication of pregnancy (4,5). Dental caries might be the result of desire for sugar, also the risk of periodontal diseases increases by higher concentration of hormones (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, oral health during pregnancy can affect the pregnancy outcome too (3,4). Preterm birth is one potential complication of pregnancy (4,5). Dental caries might be the result of desire for sugar, also the risk of periodontal diseases increases by higher concentration of hormones (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Unawareness of dental care importance is one of the factors challenging dental services during pregnancy (5). Nevertheless, most expecting women seek health care, and this period is an ideal time to offer a variety of health interventions (2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tarannum et al [29] found more general dental practitioners were aware of the association between periodontal disease and pre-term births than general medical practitioners and gynecologistS. Similarly, another study found dentists or health professionals with specialized training had more favorable attitudes towards pregnant women's oral health compared to obstetricians/ gynecologists and nurses [30,31]. In this study, not only were obstetric providers not aware of the specific issues related to pregnancy and oral health care, but they also reported having satisfactory oral health care knowledge, and were less likely to refer patients or use a multi professional approach [30].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…2 Fetal exposure to oral pathogens may increase risk of subsequent neonatal intensive care admission. 3 Maternal attitudes and behaviors towards oral hygiene and dietary practice also may influence this risk. 4 Studies have reported that barriers due to dentist and patients factors contribute to low rates of service utilization.…”
Section: Introductionmentioning
confidence: 99%
“…2 According to dentist's, high levels of perceived time and economic costs, dissatisfaction with compensation by insurers, staff resistance, skill/training costs and peer pressure from physicians are significant barriers to provision of care for pregnant patients. 3 Dentists' attitudes also have significant negative impacts as dentists with incorrect knowledge may perceive substantial barriers, thus avoiding care of pregnant patients. 3 Most of the women do not consider it important to have a dental check up during pregnancy.…”
Section: Introductionmentioning
confidence: 99%